Tumor invasion in draining lymph nodes is associated with Treg accumulation in breast cancer patients - Nicolas Gonzalo Núñez (Nature Portfolio, 2020)
Tumor-draining lymph nodes are often the first site of metastasis in breast cancer patients. Here, the authors show that metastatic lymph nodes are characterized by the accumulation of suppressive regulatory T cells with a distinct phenotype compared to matched non-invaded lymph nodes and tumors.